2019
DOI: 10.1042/bst20180590
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic regulatory features of the protein tyrosine kinases

Abstract: The SRC, Abelson murine leukemia viral oncogene homolog 1, TEC and C-terminal SRC Kinase families of non-receptor tyrosine kinases (collectively the Src module kinases) mediate an array of cellular signaling processes and are therapeutic targets in many disease states. Crystal structures of Src modules kinases provide valuable insights into the regulatory mechanisms that control activation and generate a framework from which drug discovery can advance. The conformational ensembles visited by these multidomain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 126 publications
0
23
0
Order By: Relevance
“…Protein kinases (PTKs) act like a person flipping a molecular switch to control whether proteins are turned on or off. Kinases accomplish this by facilitating the transfer of a phosphate group from ATP to either a serine, threonine or tyrosine residue of their target protein [ 7 , 8 ]. BTK is one of the five Tec family kinases, a group of cytosolic kinases that phosphorylate tyrosine residues.…”
Section: Bruton’s Tyrosine Kinase Structure and Regulationmentioning
confidence: 99%
“…Protein kinases (PTKs) act like a person flipping a molecular switch to control whether proteins are turned on or off. Kinases accomplish this by facilitating the transfer of a phosphate group from ATP to either a serine, threonine or tyrosine residue of their target protein [ 7 , 8 ]. BTK is one of the five Tec family kinases, a group of cytosolic kinases that phosphorylate tyrosine residues.…”
Section: Bruton’s Tyrosine Kinase Structure and Regulationmentioning
confidence: 99%
“…However, ADAM15 has an active metalloproteinase domain which could cleave cell surface receptors that are required for optimal AM activation. In addition, ADAM15 has a cytoplasmic tail that can bind intracellular proteins including Src kinases [ 11 ] which have diverse activities in regulating cell activation and survival [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…PTKs are important enzymes that catalyze substrate protein phosphorylation, where they transmit extracellular signals to the intracellular space and activate various intracellular signaling pathways that regulate processes of cell growth, differentiation, metabolism, migration, and apoptosis [24]. Also, studies suggested that they control the abnormal signaling transduction of cells under ischemia conditions [25][26][27].…”
Section: Discussionmentioning
confidence: 99%